2021
DOI: 10.18510/hssr.2021.9228
|View full text |Cite
|
Sign up to set email alerts
|

Do Personality and Gender Mitigate the Adverse Effects of Emotional Labor? Empirical Evidence From Healthcare During Covid-19 Pandemic

Abstract: Purpose: The impact of emotional labor on organizational outcomes is contingent upon numerous factors. Moreover, after the outbreak of the COVID-19 pandemic worldwide, the implications of emotional labour practices, especially among physicians, have become more uncertain. This study aims to address these notions by examining the multigroup moderating effect of social and enterprising personalities and gender on a model of emotional labour. The aim is to determine whether emotional labour affects emotional exha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
(50 reference statements)
0
1
0
1
Order By: Relevance
“…For example, several studies investigating the effectiveness of interventions on reducing burnout have explored the relationship between personality and burnout ( 7 ). More specifically, previous studies have found that the personality trait of neuroticism is linked to an increased risk of burnout, whereas emotional stability is linked to better implementation of coping strategies and ultimately better well-being ( 6 , 8 10 ). Ultimately, when designing and evaluating the effectiveness of interventions to reduce physician burnout, researchers and practitioners alike should take into consideration the factors mentioned above to ensure greater precision around intervention effectiveness for various groups of physicians ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, several studies investigating the effectiveness of interventions on reducing burnout have explored the relationship between personality and burnout ( 7 ). More specifically, previous studies have found that the personality trait of neuroticism is linked to an increased risk of burnout, whereas emotional stability is linked to better implementation of coping strategies and ultimately better well-being ( 6 , 8 10 ). Ultimately, when designing and evaluating the effectiveness of interventions to reduce physician burnout, researchers and practitioners alike should take into consideration the factors mentioned above to ensure greater precision around intervention effectiveness for various groups of physicians ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…있었다[2][7][8][14][15][16][17]. 코로나19 대유행 시기 근로자가 감정노동을 수행하면 정서적 긴장과 피로가 급증하여 소진 및 탈진이 초래될 가능성이 높았다[7][14]. 코로나19 대유행은 근로자에게 정서적 사건으로써 두려움과 불안으로 작용했고 감정노동에 대해 보다 부적응적인 행동전략을 채택하게 하였다[2][15-17].…”
unclassified